"Peer Support" intervention to improve glycemic control in type 2 diabetes mellitus: A literature review - Hasrima Hasrima; Elly Lilianty Sjattar; Andi Masyitha Irwan (Journal of Community Empowerment for Health, 2021)
Hyperglycemia is one of the complications of Type 2 Diabetes Mellitus (T2DM). Continuation of this situation in T2DM will lead to more serious complications such as morbidity and death. There are improvements and advances in the management of T2DM at present, but they are accompanied by an increase in medical costs. To solve these problems, an organized approach is needed to control hyperglycemia through peer support interventions which are considered to be able to reduce treatment costs. Peer support may take advantage of the ability of diabetes patients to support each other in managing their daily lives, which is very useful as a step to promote the type of daily behavioral efforts needed to prevent disease progression. This study aimed to identify the effect of peer support intervention in improving glycemic control in patients with T2DM. This study was a literature review using seven databases including PubMed, ScienceDirect, ProQuest, Clinical Key, Cochrane, Ebsco, and DOAJ. Inclusion criteria were: articles published in the last 10 years, in full text and in English version. Five studies were reviewed that met the inclusion criteria. The results of this review showed the effectiveness of peer support in improving glycemic control in diabetes patients. Peer support significantly lowered HbA1c and also led to a significant reduction in fasting blood sugar. Peer support may reduce glycosylated blood hemoglobin levels, increase knowledge regarding insulin use and increase diabetes self-management skills, especially in patients who do not have literacy skills. In conclusion, peer support can be used as a non-pharmacological therapy to improve glycemic control in patients with T2DM.